Preschool Age Children's Learning Indonesian Language Through Songs at PGRI Biru Kindergarten, Kahu District, Bone Regency - Muh. Safar (Ridwan Institute, 2023)
This research aims to describe 1) the process of learning Indonesian for preschool aged children through songs at PGRI Biru Kindergarten, Kahu District, Bone Regency and 2) Indonesian vocabulary whose meaning can be understood by preschool aged children which is acquired through songs at the park. PGRI Biru Children, Kahu District, Bone Regency. This research is a qualitative descriptive study using all learning activities and all the vocabulary contained in the songs used in PGRI Biru Kindergarten learning, Kahu District, Bone Regency. The data source is oral data from teachers and children of PGRI Biru Kindergarten, Kahu District, and Bone Regency and from songs used in learning. Data collection techniques were carried out using library and field techniques consisting of direct observation, interviews and recording. The results of the research show that the process of learning Indonesian through songs at PGRI Biru Kindergarten, Kahu District, Bone Kabupaten shows that of the 96 Indonesian words taught through songs, there are 70 words or 66.04% whose meaning can be understood by all children and 26 words or 33.96% whose meaning some children cannot understand. Thus it can be concluded that 1) the process of learning Indonesian through songs at the PGRI Kindergarten, Kahu District, and Bone Regency is applied to preschool children using imitation and play techniques. 2) Some of the vocabulary can be understood by all children and some words cannot be understood by the meaning of some children.